Upward flame spread over discrete thick fuels under mixed convection flow. (February 2023) - Zhang, Yue; Fang, Jun; Tian, Fengyuan; Song, Lei; Singh, Ajay V.
Abstract: In this paper, flame spread over a vertically oriented discrete fuel array is investigated experimentally under mixed-convective flow conditions, using polymethyl methacrylate (PMMA) as the solid fuel. It is found that under mixed convective conditions, the flame propagation over a discrete fuel array can be categorized into three regimes with decreasing fuel coverage. The flame spread rate is observed to exhibit a positive relationship with fuel coverage and fuel length. The limiting fuel coverage ratio that supports the flame spread reduces with the length of fuel blocks. Meanwhile, a peak value of mass flux is observed at a fuel coverage value below unity due to a delayed thickening of the thermal boundary layer with the inert insulation board effects. This indicates that the distribution of discrete fuel array in addition to fuel properties and fuel loading significantly affects the flame spread rate and the risks associated with it. Additionally, the flame spread model can accurately predict the flame spread rate and the onset of limiting conditions for the flame spread over a discrete fuel array under mixed-convective conditions. The results of this paper may be crucial for developing effective mitigation strategies for fire safety in façades, wildland, and urban environments.